2007
DOI: 10.1007/s00299-007-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new ABA- and MEJA-activated sugarcane bZIP genes by data mining in the SUCEST database

Abstract: Sugarcane is generally propagated by cuttings of the stalk containing one or more lateral buds, which will develop into a new plant. The transition from the dormant into the active stage constitutes a complex phenomenon characterized by changes in accumulation of phytohormones and several other physiological aspects. Abscisic acid (ABA) and methyl-jasmonate (MeJA) are major signaling molecules, which influence plant development and stress responses. These plant regulators modulate gene expression with the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 65 publications
0
23
0
1
Order By: Relevance
“…Basic leucine zipper (bZIP) transcription factors regulate physiological and stress responses. According to Schlögl et al (2008), ABA regulates six sugarcane bZIPs, with two genes being up-regulated ( ScbZIP29 and ScbZIP31 ) and four genes down-regulated ( ScbZIP21, ScbZIP24, ScbZIP70 , and ScbZIP79 ) in sugarcane plants exposed to ABA in vitro . The authors suggested a model where ABA-activated kinase proteins activate or stabilize bZIPs proteins by phosphorylation, which in turn could bind to cis -elements (e.g., ABRE and/or DRE), controlling gene expression (Schlögl et al, 2008).…”
Section: Drought Stress and Aba Signalingmentioning
confidence: 99%
“…Basic leucine zipper (bZIP) transcription factors regulate physiological and stress responses. According to Schlögl et al (2008), ABA regulates six sugarcane bZIPs, with two genes being up-regulated ( ScbZIP29 and ScbZIP31 ) and four genes down-regulated ( ScbZIP21, ScbZIP24, ScbZIP70 , and ScbZIP79 ) in sugarcane plants exposed to ABA in vitro . The authors suggested a model where ABA-activated kinase proteins activate or stabilize bZIPs proteins by phosphorylation, which in turn could bind to cis -elements (e.g., ABRE and/or DRE), controlling gene expression (Schlögl et al, 2008).…”
Section: Drought Stress and Aba Signalingmentioning
confidence: 99%
“…In silico EST analyses were also used for selection of sugar transporters that are apparently modulated during stem maturation as validated by northern blot hybridization (Casu et al 2003(Casu et al , 2004. In a macroarray analysis of randomly selected sugarcane cDNAs, it was possible to identify candidate genes whose expression was modulated by low temperature, methyl-jasmonate and ABA treatment of the plants (Nogueira et al 2003;Rosa et al 2005;Schlögl et al 2008). Similarly, Rocha et al (2007) used a signal transduction-oriented microarray analysis to better understand phytohormones and environmental challenges in sugarcane and found 179 differentially regulated genes.…”
Section: Gene Discovery and Sugarcane Genomicsmentioning
confidence: 99%
“…Expression of bZIP genes has been shown to be modulated by ABA (Lee et al, 2006;Zou et al, 2008), methyl-jasmonate (MeJA) (Schlögl et al, 2008), as well as various abiotic and biotic stress treatments, including salt (Nijhawan et al, 2008;Zou et al, 2008), cold (Lee et al, 2006;Nijhawan et al, 2008;Zou et al, 2008), dehydration (Nijhawan et al, 2008;Rodriguez-Uribe and O'Connell, 2006), methyl viologen (MV) and pathogen infection (Lee et al, 2006). In combination, these results suggest that bZIP factors play important roles in the stress response of plants.…”
Section: Introductionmentioning
confidence: 95%